Lobelia chinensis Extract and Its Active Compound, Diosmetin, Improve Atopic Dermatitis by Reinforcing Skin Barrier Function through SPINK5/LEKTI Regulation - Park, No-June; Jo, Beom-Geun; Bong, Sim-Kyu; Park, Sang-A; Lee, Sullim; Kim, Yong Kee; Yang, Min Hye; Kim, Su-Nam (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The skin acts as a mechanical barrier that protects the body from the exterior environment, and skin barrier function is attributed to the stratum corneum (SC), which is composed of keratinocytes and skin lipids. Skin barrier homeostasis is maintained by a delicate balance between the differentiation and exfoliation of keratinocytes, and keratinocyte desquamation is regulated by members of the serine protease kalikrein (KLK) family and their endogenous inhibitor SPINK5/LEKTI (serine protease inhibitor Kazal type 5/lympho-epithelial Kazal-type-related inhibitor). Furthermore, SPINK5/LEKTI deficiency is involved in impaired skin barrier function caused by KLK over-activation. We sought to determine whether increased SPINK5/LEKTI expression ameliorates atopic dermatitis (AD) by strengthening skin barrier function using the ethanol extract of Lobelia chinensis (LCE) and its active compound, diosmetin, by treating human keratinocytes with UVB and using a DNCB-induced murine model of atopic dermatitis. LCE or diosmetin dose-dependently increased the transcriptional activation of SPINK5 promoter and prevented DNCB-induced skin barrier damage by modulating events downstream of SPINK5, that is, KLK, PAR2 (protease activated receptor 2), and TSLP (thymic stromal lymphopoietin). LCE or diosmetin normalized immune response in DNCB treated SKH-1 hairless mice as determined by reductions in serum immunoglobulin E and interleukin-4 levels and numbers of lesion-infiltrating mast cells. Our results suggest that LCE and diosmetin are good candidates for the treatment of skin barrier-disrupting diseases such as Netherton syndrome or AD, and that they do so by regulating SPINK5/LEKTI.